Save Energy With Anti‐Stagnation Valves. Issue 8 (5th August 2019) - Alberton, Dave; Sucharda, Peter
Abstract : The city of Hamilton's water distribution system is one of Canada's oldest and most complex water distribution systems. Situated at the west end of Lake Ontario, the city has an elevation of 298 ft (91 m) above sea level and is defined by unique geographical features, including the Niagara Escarpment and the Hamilton Harbor.